PENGARUH KETERSEDIAAN SUMBERDAYA IT TERHADAP MOTIVASI PENGGUNAAN BALANCED SCORECARD (BSC) DAN DAMPAKNYA PADA KINERJA ORGANISASI SEKTOR PUBLIK DI SAMARINDA - Yulia Tri Kusumawati; Praja Hadi Saputra (Jurnal Ekonomi dan Manajemen, 2019)
The research entitled "The Effect of the Availability of IT Resources on the Motivation of the Use of BSC and Its Impact on Public Sector Organizational Performance in Samarinda", aims to find out about the factors that motivate managers to use the Balanced Scorecard (BSC) in public organizations in Samarinda and then see the impact The BSC is about organizational performance. Data is taken using survey techniques. The sample from this study was SKPD leaders in Samarinda city with a total of 45 respondents. The analysis technique used is SEM-PLS. Survey technique through a questionnaire (questionnaire) to determine the motivation of leaders (managers) using BSC. The results showed that organizational factors (availability of IT resources) were positively and significantly related to motivation to use BSC in public organizations and had an impact on improving organizational performance.